Legal Protection of Intellectual Property Rights for Small Businesses in the Songket Craft Industry in Batu Bara Regency - Fadhillah; Saidin; Syarifah Lisa Andriati (International Journal of Economic, Technology and Social Sciences (Injects), 2024)
Batu Bara Songket is a cultural heritage that must be maintained and preserved, not only because of its historical and traditional value, but also its role in the social and economic life of the Batu Bara Malay community. Legal protection for songket craftsmen and business actors is very necessary to prevent unethical practices such as piracy and counterfeiting, which can harm both producers and consumers. With these protection efforts, the sustainability of traditional songket production can be guaranteed, while also making a significant contribution to regional economic development and the preservation of national culture.